Analisis Faktor Stres Pada Kinerja Sumber Daya Manusia - Wiharjanto, Danang; Rusmana, Roni; Suharyat, Yayat (LPPM Institut Pendidikan Nusantara Global, 2024)
Stress is a phenomenon experienced due to the internal pressure within individuals. The purpose of this journal is to provide a description of stress management among employees. The methodology employed in this journal utilizes a qualitative approach, collecting data in the form of words, sentences, or phrases. The data gathered is secondary data obtained by the author from relevant books, journals, or research articles. The research indicates that stress arises from various factors, whether environmental, organizational, or individual, ultimately leading to a decrease in employee work productivity. Failure to manage stress properly can exacerbate the situation. In conclusion, this paper emphasizes the need for appropriate stress management for individuals experiencing stressful conditions. By doing so, their situation can be controlled, enabling employees to enhance their work productivit. The dynamics of stress in the workplace can have both positive and negative impacts, not only being a stimulus for workers to feel more enthusiastic and motivated, but can also cause a decrease in productivity and various health problems if not managed properly. Stress management is essential in maintaining a healthy work environment and ensuring employee well-being.